Prisões do Norte: reflexões sobre o serviço social e a atuação do assistente social no sistema prisional - Coutinho, Wellington Macedo (Universidade Federal do Tocantins, 2022)
This Course Conclusion Work aims to bring elements that allow a re flection on the role of the social worker in the prison system, through the existing possibilities for the development of their professional practice and the reality present in Brazilian pen itentiary parks, specifically in the Region North of Brazil. For t his purpose, interviews with social workers were carried out within the scope of the research “Diagnostic of Prison Services in Brazil”, in addition to a review of bibliography relevant to t he theme and data from the National Survey of Prison Information ( INFOPEN). This course conclusion work is justified by the need to apprehend the professional practice of Social Work, through the existing contradictions in the socio legal area and in the r eality of prison. Being, above all, essential a critical look for a radical understanding of this reality, because in the socio juridical universe the social worker deals directly with the process of criminalization of the "social question", as well as ins erts himself in the midst of the basic relations of support of the capitalist mode of production. . By understanding the prison as an institution of control, it presents to the Social Service, several challenges and possibilities, in this sense we will see k to understand the processes that relate to the professional perf ormance of the social worker in the search for the effectiveness of his professional praxis, as well as, to weigh on the relationship between professional practice and the Penal Execution La w (LEP).